Beyond multidrug-resistant tuberculosis in Europe: a TBNET study - Günther, G (2015)
The emergence of drug-resistant tuberculosis (TB) is a challenge to TB control in Europe. We evaluated second-line drug susceptibility testing in Mycobacterium tuberculosis isolates from patients with multidrug-resistant, pre-extensively drug-resistant (pre-XDR-TB) and XDR-TB at 23 TBNET sites in 16 European countries. Over 30% of bacilli from patients with pre-XDR-TB showed resistance to any fluoroquinolone and almost 70% to any second-line injectable drug. Respectively >90% and >80% of the XDR-TB strains tested showed phenotypic resistance to pyrazinamide and ethambutol. Resistance to prothionamide/ethionamide was high in bacilli from pre-XDR-TB patients (43%) and XDR-TB patients (49%).